2019
DOI: 10.1111/j.1755-3768.2019.5425
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress induces mitochondrial dysfunction and autophagy in ARPE‐19 cells

Abstract: Purpose Oxidative stress plays an important role in the pathogenesis of age‐related macular degeneration (AMD), but the exact mechanism of the influence of the stress is not completely clear. The stress can affect both neural retina and retinal pigment epithelium (RPE) cells The purpose of our study was to evaluate changes in some mitochondrial properties and autophagy in the response of RPE cells to oxidative stress. Methods Retinal pigment epithelium ARPE‐19 cells were challenged with 200 mM H2O2 for 2 h. Mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Earlier studies have effectively described the vital role of oxidative stress by H 2 O 2 in inhibiting cell proliferation in various cells [ 62 ], including RPE in the retina [ 35 , 46 , 63 , 64 ]. The exact mechanisms have not been identified, however, recent studies have revealed the interference of H 2 O 2 in numerous intracellular signaling pathways in retinal epithelial cells, such as the epidermal growth factor receptor/AKT and Notch signaling pathways [ 46 , 64 ], including the regulation of autophagy [ 65 ], kinases, and pro-apoptotic proteins such as caspases [ 66 , 67 , 68 ]. These studies open the way towards future identification of the mechanisms involved in the interplay between vitamin D and retinal cells in restoring cell proliferation and protecting RPE from angiogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies have effectively described the vital role of oxidative stress by H 2 O 2 in inhibiting cell proliferation in various cells [ 62 ], including RPE in the retina [ 35 , 46 , 63 , 64 ]. The exact mechanisms have not been identified, however, recent studies have revealed the interference of H 2 O 2 in numerous intracellular signaling pathways in retinal epithelial cells, such as the epidermal growth factor receptor/AKT and Notch signaling pathways [ 46 , 64 ], including the regulation of autophagy [ 65 ], kinases, and pro-apoptotic proteins such as caspases [ 66 , 67 , 68 ]. These studies open the way towards future identification of the mechanisms involved in the interplay between vitamin D and retinal cells in restoring cell proliferation and protecting RPE from angiogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…H 2 O 2 was chosen to induce oxidative stress in ARPE-19 cells because ARPE-19 cells have a high metabolic rate and exist in an environment that is abundant in endogenous ROS, such as O2-, H 2 O 2 and OH-. Long-term accumulation of oxidative damage leads to dysfunction of RPE cells and increases their susceptibility to oxidative stress [ 47 , 48 ]. H 2 O 2 is one of the most common oxidants used in the cellular oxidative stress models for ARPE-19 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Under oxidative stress TERT can shuttle from the nucleus to mitochondria where it exerts a protective action on mitochondrial DNA (mtDNA) against various stresses [42,43]. These activities of telomerase are important in the context of AMD pathogenesis, in which oxidative stress and mitochondria play a crucial role [44].…”
Section: Telomeres and Telomerase In Amdmentioning
confidence: 99%
“…In fact, several studies show a greater susceptibility of mtDNA than nDNA in AMD (e.g., [71][72][73][74]). Differences in the susceptibility between mtDNA and nDNA to DNA-damaging factors, especially of endogenous origin, in normal conditions are mainly determined by the differences in their metabolism and DDR mechanisms in mitochondria and the nucleus (reviewed in [44]). Moreover, methods used to measure DNA damage in these two organelles are usually different.…”
Section: Dna Damage Responsementioning
confidence: 99%